Adverse effect of catechol-O-methyltransferase (COMT) Val158Met met/met genotype in methamphetamine-related executive dysfunction. (November 2019) - Cherner, Mariana; Watson, Caitlin W.-M.; Saloner, Rowan; Halpin, Laura E.; Minassian, Arpi; Murray, Sarah S.; Vaida, Florin; Bousman, Chad; Everall, Ian
Abstract: Introduction: The Val allele of the Val158Met single-nucleotide polymorphism of the catechol- o -methyltransferase gene ( COMT ) confers greater catabolism of dopamine (DA) in the prefrontal cortex (PFC) than the Met allele. Met/Met homozygotes typically outperform Val-carriers on tests of executive function (EF), perhaps resulting from increased DA bioavailability. Methamphetamine (METH) causes large releases of DA, which is associated with neurotoxicity and executive dysfunction in chronic METH users. We hypothesized that, contrary to its effect in non-METH-using populations, slower DA clearance conferred by Met/Met will relate to worse EF in METH users. Methods: 149 non-Hispanic White men, stratified by METH dependence (METH+/−) and COMT (Val/Val, Val/Met, Met/Met), completed three tests of EF: Wisconsin Card Sorting Test (WCST), Stroop Color-Word Test (Stroop), and Trail Making Test Part B (Trails B). Demographically-adjusted test scores were averaged to create an EF composite T-score. We examined the interaction of METH and COMT on the EF composite and individual test T-scores, controlling for premorbid functioning and alcohol use. Results: METH group differences in EF were evident only among Met/Met carriers (beta = −9.36, p < .001) but not among Val carriers: Val/Met (beta = −1.38, p = .44) and Val/Val (beta = −4.34, p = .10). These effects were most salient on the WCST. Conclusions: In the pre-frontal hyperdopaminergic state triggered by methamphetamine, greater DA inactivation conferred by the Val allele may protect against METH-related executive dysfunction, suggesting genetically-driven differences in vulnerability to METH. Highlights: Executive dysfunction in methamphetamine users varies by COMT Val158Met genotype. Methamphetamine effects on executive function are seen only in Met/Met carriers. Val carriers have similar executive function irrespective of methamphetamine use. Slower dopamine clearance conferred by Met is a liability in methamphetamine use. COMT-controlled prefrontal dopamine bioavailability impacts methamphetamine injury.